2001
DOI: 10.1055/s-2001-16244
|View full text |Cite
|
Sign up to set email alerts
|

Food Restriction, Performance, Psychological State and Lipid Values in Judo Athletes

Abstract: Dietary intake, plasma lipids, lipoprotein and apolipoprotein levels, anthropometric measurements and anaerobic performance were studied in eleven judo athletes during a period of weight maintenance (T1) and after a 7d food restriction (T2). Dietary data were collected using a 7-day diet record. Nutrient analysis indicated that these athletes followed a low carbohydrate diet whatever the period of the investigation. Moreover, mean micronutrient intakes were below the French recommendations. Food restriction re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
148
5
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 34 publications
16
148
5
14
Order By: Relevance
“…Although previous studies have pointed out the negative effect of rapid weight loss on mood [37,38], in the present study there was no difference in humor profile components (tension, depression, anger, vigour, fatigue and confusion) between the weighing and one hour pre-match moments.…”
Section: Discussioncontrasting
confidence: 92%
“…Although previous studies have pointed out the negative effect of rapid weight loss on mood [37,38], in the present study there was no difference in humor profile components (tension, depression, anger, vigour, fatigue and confusion) between the weighing and one hour pre-match moments.…”
Section: Discussioncontrasting
confidence: 92%
“…A previous investigation found a positive correlation between the dehydration level and cortisol concentration, whereas a negative correlation was observed between dehydration and total testosterone [7]. Filaire et al [8] observed impairments in performance, differences in the nutritional state (proteins and macronutrients), and increased aggressiveness after the rWL procedure. Malnutrition leads to body weight loss, since it reduces the glycogen stores, and may prejudice the performance [26], mainly in high intensity efforts, commonly associated with attack and defence actions in judo.…”
Section: Discussionmentioning
confidence: 99%
“…Drastic body weight reduction before competition has been associated with physical performance impairment in judo athletes [8]. According to the authors, there are alterations in basal metabolism, muscular glycogen, aerobic capacity, cardiac output, and the immunological system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Judokas spend significantly high amount of energy during the training and competitions which affects energy balance, hormonal profile and metabolic hemostasis (Filaire et al, 2001). There was a limited number of studies related females judokas in the literature (Prouteau et al, 2007).…”
Section: Introductionmentioning
confidence: 99%